Pratiques enseignantes et réalité professionnelle : cas d'enseignants des lycées techniques et professionnels industriels au Gabon - EMMANUEL MOUDOUMA; JACQUES GINESTIÉ; HÉLÈNE CHENEVAL-ARMAND (Metaichmio Publications, 2011)
This article presents the outcomes of a study on the practises of Gabonese teachers who teach in the fields of industrial technical and vocational education. This study is interested in their daily activities and aims at characterising the inevitable variation which exists between the knowledge with work in the production activities industrial in company and those implemented in the institutions of vocational training. More generally, it is a question of appreciating the relation between training and employment. Thus, we are interested in the orientation given by the teacher to his daily practise to reduce or not this variation. The results of this study highlight the impact of epistemological and pragmatic dimensions on the organisation of the activities and thus on the practises. Obviously, the level of entry in the technical school course, the first job, the transport conditions, the appropriation of the reference frame of training and the development of the contents of courses are some of the items which impact this process of reduction of the difference between the two forms of knowledge.